MoS2: Acoustic–Excitonic Coupling for Dynamic Photoluminescence Manipulation of Quasi‐2D MoS2 Nanoflakes (Advanced Optical Materials 7/2015). Issue 7 (July 2015) - Rezk, Amgad R.; Walia, Sumeet; Ramanathan, Rajesh; Nili, Hussein; Ou, Jian Zhen; Bansal, Vipul; Friend, James R.; Bhaskaran, Madhu; Yeo, Leslie Y.; Sriram, Sharath
<x xml:space="preserve">Abstract</x> S. Sriram and co‐workers report a new way to control the photoluminescence (PL) response in atomically thin, quasi‐2D molybdenum disulphide. On page 888, it is shown that high‐frequency surface acoustic waves alter the behaviour of charge carriers, interfering with the time lag between photon absorption and light emission. This mechanism is exploited to controllably modulate the PL.